Integrated Governance Mechanisms for Empowerment and Resilience in International Food Value Chains - Juan Manuel Ramon-Jeronimo; Ana Cruz Gonzalez-Calzadilla; Amparo Graciani-Herrero; Raquel Florez-Lopez (Foods, 2023)
Considering the significance of the food sector in recent years, the main objective of this Special Issue is to identify the most appropriate governance mechanisms (formalized and relational) for the management of collaborative networks among the international chain of food companies, which are increasingly subject to greater risks and disruptions [...]